Numerical Solution of Flow and Heat Transfer over a Stretching Sheet with Newtonian Heating using the Keller Box Method - Norhafizah, Md Sarif; Mohd Zuki, Salleh; Roslinda, Nazar (Elsevier Ltd, 2013)
In this paper, the steady boundary layer flow and heat transfer over a stretching sheet with Newtonian heating in which the heat transfer from the surface is proportional to the local surface temperature is studied. The nonlinear boundary layer equations are transformed into ordinary differential equations which are then solved numerically via the Keller box method. Numerical solutions are obtained for the wall temperature and the local heat transfer coefficient for various values of the Prandtl number and the conjugate parameter γ.